2014
DOI: 10.3747/co.21.1773
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Documentation of Palliative Sedation: A Quality Improvement Initiative

Abstract: ConclusionsThe lack of documentation and standardized practice of ps on our pcu has resulted in a quality improvement program to address those gaps. They also highlight the importance of conducting research and developing clinical guidelines in this area. KEY WORDSPalliative care, conscious sedation, deep sedation, documentation, hypnotics and sedatives BACKGROUNDPalliative sedation (ps) is the intentional, continuous use of sedative medications with the goal of reducing consciousness and relieving intolerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The review concluded that there is an urgent need "to resolve the conceptual confusion that currently exists in the literature." That comment by the authors about the possibility that terminology confusion is, in the end, a reflection of confusion in clinical practice resonates very well with the quality improvement report by McKinnon et al 1 .…”
Section: Rl Fainsinger Md*supporting
confidence: 69%
See 1 more Smart Citation
“…The review concluded that there is an urgent need "to resolve the conceptual confusion that currently exists in the literature." That comment by the authors about the possibility that terminology confusion is, in the end, a reflection of confusion in clinical practice resonates very well with the quality improvement report by McKinnon et al 1 .…”
Section: Rl Fainsinger Md*supporting
confidence: 69%
“…In view of increasing interest in that topic and some of the surrounding controversy, the presentation in this issue of Current Oncology of a quality improvement report by McKinnon et al 1 on the use and documentation of the practice in their palliative care setting is timely and arguably a wake-up call to other programs. Those authors identified a number of documentation deficits and the need to implement guidelines that standardize charting and staff education.…”
Section: Rl Fainsinger Md*mentioning
confidence: 99%
“…Large variations in PS practice are found and, as a result, clinical performance still differs (24,25). Additionally, a lack of documentation and standardized practice of PS was apparent in an audit of PS practice performed as a quality improvement program (25).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a lack of documentation and standardized practice of PS was apparent in an audit of PS practice performed as a quality improvement program (25).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring all aspects of CPS is essential and widely recommended. 2,11,26,[30][31][32] Before the start of our study we analyzed the data about the different aspects of the CPS documented in the clinical diary of the patients who died in Bentivoglio Hospice. The Bentivoglio Hospice belongs to the Hospice Seràgnoli Foundation Onlus, an operational structure coordinated by the Isabella Seràgnoli Foundation, Bologna (Italy).…”
Section: 28mentioning
confidence: 99%